(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The essay aims to propose a theoretical reflection about VR Cinema, a recent artistic practice born by applying the technical and aesthetic apparatus of Virtual Reality to narrative and stylistic features of Cinema. After a brief etymological premise around the idea of immersivity, useful for circumscribing the field of investigation, we will introduce the Cinema VR, trying to analyse its media nature describing it through some reflections by Citton and by Auslander. We then will focus on Carbone’s “philosophy-screens”, trying to associate the “sensitive idea” of “arche-screen” with the Cinema VR, through a discussion on the perception between body and screen. In the end, after some clarifications of a technical nature, we will return to the theoretical exploration using the analysis of D’Aloia. In this way we will try to explain what we developed throughout the discussion, highlighting also possible future extensions.